FIGARCH Processes: Estimation on volatility in exchange rates of Per´u - Briones Zúñiga, José Luis (2019)
This research presents a theoretical review of the structure and applica-tion of long memory nature models that combine characteristics of the fractionally integrated processes with the classic GARCH models, thus obtaining the autoregres-sive models with fractionally integrated conditioned heterocedasticity (FIGARCH) which Through the cumulative response impulse function, I can quantify the degree of persistence of the impact of innovation on the function of conditioned variance, that is, the element of persistence in a chaotic series very sensitive to changes in initial conditions associated with fractional Brownian motion. For this application, the exchange rate variable was used, and by means of long memory time series mo-dels, the persistence of the existing eﬀect on the volatility of said series could be analyzed.